A 2-D Space-Variant Chirp Scaling Algorithm Based on the RCM Equalization and Subband Synthesis to Process Geosynchronous SAR Data - Sun, Guang-Cai; Xing, Mengdao; Wang, Yong; Yang, Jun; Bao, Zheng (IEEE transactions on geoscience and remote sensing, 2014)
A space-variant chirp scaling algorithm based on the range cell migration (RCM) equalization and azimuth subband synthesis has been studied to process simulated geosynchronous synthetic aperture radar (GEO-SAR) data. The acceptable order of terms in polynomials for the slant range models in the RCM correction and phase error compensation, division of subband, and suppression of grating lobes of the subbands was investigated. Qualitatively and quantitatively, the method was able to focus simulated GEO-SAR signals well. Finally, the constraint on the spatial extent of azimuth and range dimensions using the algorithm was assessed.